ANALISIS RASIO KEUANGAN PERUSAHAAN PT. SALIM IVOMAS PRATAMA TBK PERIODE TAHUN 2018-2022 - T, Bryan Adrians (Universitas Widya Kartika Surabaya, 2024)
This research aims to determine whether the financial performance of PT. Salim Ivomas Pratama periode 2018-2022 is in condition good or bad measured using liquidity, solvability, profitability and activity ratios. This type of research method uses a descriptive quantitative approach. The population chosen in this research is all companies that diligently publish their financial reports every year online, by determining the sample using purposive sampling, so acquiring the company PT. Salim Ivomas Pratama periode 2018-2022. The analysis technique used is descriptive kuantitative from the results of ratio calculations and then compared based on existing industry ratio standards so that it can be concluded that the liquidity, profitability and activity conditions of PT. Salim Ivomas Pratama is in poor condition while its solvability condition is quite good.